Risk Factor Analysis of Covid-19 in Children: Literature Review - Musviro Musviro; Siti Rohania; Nurul Hayati; Rizki Dwi Fibriansari (Universitas Bondowoso, 2022)
Introduction: COVID-19 is currently a serious disease in many countries around the world. A children are one of the vulnerable groups for COVID-19 transmission. One of the ways to prevent the occurrence of COVID-19 in children is by knowing the risk factors for the occurrence of COVID-19 in children. The purpose of this study was to analyze the risk factors for the occurrence of COVID-19 in children. Method: The method used in the preparation of the Literature review using PICOS. The secondary data obtained came from journals with a predetermined discussion. Based on the results of a literature search through six databases. Researchers get 447 articles that match the keywords. The researcher then screened based on the title (n=242), abstract (n=107) and full text (n=10) which were adjusted to the inclusion criteria. Result: There are 3 risk factors for the occurrence of COVID-19 in children. Family exposure is the highest risk factor because the family does not realize that they have been exposed outside the home and accidentally transmit COVID-19 to their children. The second risk factor is kunderlying health condition of the child. The child's underlying health conditions can cause symptoms that appear due to COVID-19 to be more severe. The third risk factor is immunity. The immune system in children is still low and not perfect because children are still in the developmental stage. Conclusion: Risk factors for COVID-19 in children include:family exposures, underlying health conditions, and immunity.This risk factor is a step to prevent COVID-19 in children so that this factor needs to be known by the wider community.